2016
DOI: 10.33549/physiolres.933039
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of the Training-Induced Decrease in Basal Cortisol Concentration in the Improvement in Muscular Performance in Humans

Abstract: Acute exercise-induced changes in cortisol concentration (C) and training related adaptation within hypothalamic-pituitary-adrenal (HPA) axis has been widely examined, but their influence on muscle strength performance is at best uncertain. Twenty four young healthy men were randomly assigned to an endurance training group (ET, n=12) or to a non-exercising controls (CON, n=12). ET performed supervised endurance training on cycle ergometer for 20 weeks. Endurance training program improved exercise capacity (14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…The data regarding the effect of exercise training on gonadal androgens in aging males are, however, inconsistent ( 52 , 53 ). Nevertheless, based on our earlier studies ( 20 , 26 , 54 , 55 ), we can suggest that the basal T and fT concentrations change in response to exercise training accordingly to the applied training load. Therefore, it can be postulated that a low-to-moderate training load leads to an increase in the T concentration ( 20 , 54 ), a moderate-to-heavy training load does not change it ( 26 ), and a heavy-to-maximal training load leads to a decrease in its concentration ( 55 ).…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…The data regarding the effect of exercise training on gonadal androgens in aging males are, however, inconsistent ( 52 , 53 ). Nevertheless, based on our earlier studies ( 20 , 26 , 54 , 55 ), we can suggest that the basal T and fT concentrations change in response to exercise training accordingly to the applied training load. Therefore, it can be postulated that a low-to-moderate training load leads to an increase in the T concentration ( 20 , 54 ), a moderate-to-heavy training load does not change it ( 26 ), and a heavy-to-maximal training load leads to a decrease in its concentration ( 55 ).…”
Section: Discussionmentioning
confidence: 69%
“…The data regarding the effect of exercise training on gonadal androgens in aging males are, however, inconsistent (52,53). Nevertheless, based on our earlier studies (20,26,54,55), we can suggest that the basal T and fT concentrations change in response to exercise training accordingly to the applied training load. Therefore, it can be postulated that a low-to-moderate training load leads to an increase in the T concentration (20,54) The training-induced changes in the androgen concentrations, regardless of whether they are related to the direct stimulation of the HPG axis or to the effects of body fat-androgens interactions, may be of great importance because we have demonstrated that they are inversely correlated with markers of inflammation and blood lipids (Figures 1 and 2).…”
Section: Androgens and Exercisementioning
confidence: 83%
See 2 more Smart Citations
“…The latter premise has been suggested as a result of an analysis of experiments performed in different studies. Thus, for instance, it is known that trained athletes in response to intensive physical loads ( F ″) show higher cortisol secretion [22] mainly due to the decrease in post-training value ( F′ ) of basal secretion [23, 24]. Untrained people, however, did not display such increased secretion, or even showed a decline thereof.…”
Section: Description Of the Methodsmentioning
confidence: 99%